Measures of Central Bank Autonomy : Empirical Evidence for OECD, Developing, and Emerging Market Economies - Segalotto, Jean-Francois (IMF Working Papers; Working Paper ;, 2006)
This paper presents an update of the Grilli-Masciandaro-Tabellini (GMT) index of central bank (CB) autonomy, based on CB legislation as of end-2003. The index is applied to a set of OECD and developing countries, and emerging market economies. For a smaller set of countries, the paper presents a reconstruction of the GMT index based on Cukierman (1992) and assesses changes in CB autonomy between 1992 and 2003. The results point to a significant increase in CB autonomy, in particular for developing countries. In most cases, this improvement has involved a three-stage process: an initial stage in which the political foundations for CB autonomy are laid; a second stage in which operational autonomy develops; and a final stage in which CBs gain further political autonomy in terms of policy formulation and the appointment of senior management.